Bit Preservation: A Solved Problem? - David S. H. Rosenthal (International Journal of Digital Curation, 2010)
For years, discussions of digital preservation have routinely featured comments such as â€œbit preservation is a solved problem; the real issues are ...â€. Indeed, current digital storage technologies are not just astoundingly cheap and capacious, they are astonishingly reliable. Unfortunately, these attributes drive a kind of â€œParkinsonâ€™s Lawâ€ of storage, in which demands continually push beyond the capabilities of systems implementable at an affordable price. This paper is in four parts: